Peer Effect on Environmental Information Disclosure: Evidence from High-polluting Industries in China - Ji, Zhiying; Chen, Zhuo; Chen, Jun (Recent Patents on Mechanical Engineering, 2023)
Background: Among the research on the influencing factors of environmental information disclosure, scholars rarely identify the factors from the perspective of the enterprise’s external environment, especially peer enterprise behavior. In fact, the disclosure of environmental information by most enterprises in China is still only voluntary, and the form of disclosure is so chaotic that it is easy to be influenced by other enterprises. Objective: This study aimed to determine whether a firm's EID is affected by peer firms and contribute to the existing literature on the influencing factors of EID. Methods: An analytical framework incorporating the herd behavior hypothesis, the legitimate theory, and the stakeholder theory is constructed, and fixed effect estimation, as well as a two-stage least square, is used to test the hypotheses. Results: There is a peer effect on environmental information disclosure of high-polluting firms. It has been observed that the focal firm imitates the disclosure behavior of small peer firms more than the large peer firms. Moreover, a peer effect of environmental disclosure on sensitive and non-sensitive information is also reported, but the peer effect on sensitive information is larger than that on nonsensitive information. Conclusion: First, policymakers need to realize that there is a peer effect involved in EID among highpolluting firms and improve the binding force of environmental regulations. Second, there are “demonstration effects” involved in EID. In the practice of regulations on disclosure, the smaller firms need to be under stricter scrutiny and set as models of EID to improve the efficiency of supervision and regulation. Third, enterprises have a stronger peer effect on the disclosure of sensitive information. Governments should strengthen the supervision of sensitive information disclosure.
Keywords: Peer effect